An Analysis of Multimodal Narrative and Cognitive Construction of Identity in "Are You My Mother?" Scott McCloud and Erik Erikson’s Perspectives - Merwa Khalid; Dr. Rasib Mahmood; Aqsa Atta; Bibi Halima (Journal of Management Practices, Humanities and Social Sciences, 2021)
For the past few decades, multimodal narratives hold a unique place in the contemporary world of literature. These distinctive trends of narratives are preoccupied with the representation of highly verbalized self-consciousness and cognitive development of identity. Taking the theoretical concepts of Scott McCloud and Erik Erikson into consideration, this paper explores the visual and verbal expression of Bechdel’s Are You My Mother? to understand the presentation of cognition in a mixed-media environment of the graphic novel. This study is limited to the focal character of the graphic novel, and selected eight images are analyzed to answer research questions. McCloud’s theoretical model deals with visual structure whereas, Erickson's conceptions examine verbal expression of the novel. The findings reveal that both pictorial and written assertion of the selected narrative is overbrimming with dispersed references to the character’s cognitive state. Moreover, it also inspects Bechdel’s complex personality; she struggles hard to resolve her psychosocial crisis in different stages of life but succeeds in accepting and maintain her identity through the therapeutic process and writing. This study is also a call for those who think reading comics is labor; it tracks the way for readers to reach the cognitive functioning of characters in multimodal narratives.